Andreas Haarder: Beowulf. The appeal of a poem. Akademisk forlag. 1975 - Kruuse, Jens (Grundtvig-studier, 1975)
Andreas Haar der: Beowulf. The Appeal of a. Poem Reviewed by Jens Kruuse Dr. Jens Kruuse’s review of this doctorate, which was defended with great distinction at Aarhus University in March 1975, consists partly of a brief characterization of the poem itself, and partly of a summary of Haarder’s interpretation seen in relation to the highly divergent assessments of the poem by recent English and French critics. The doctorate is shown to be particularly relevant in its debt to Grundtvig’s repeated discussions of the poem. Beowulf is not just a museum piece but a mythical picture of a philosophy of life that still concerns both researchers and readers of tne poem to a considerable degree.The life of man is presented as a well-ordered room with fixed limits, surrounded by a chaotic world in which inhuman monsters play their foul tricks. There is a risk that a monster can take control over human life; even worse, a human being may become a monster. But it is always possible for the hero to defeat, wound and kill the monster – in the end losing his own life, however.The basic principle of the doctorate is that the poem came into being as a living expression of the interplay between the creating poet and the listening audience, a consideration that immediately recalls Grundtvig. The book, according to Jens Kruuse, is »a rare thing - a piece of solid humanistic research sustained by a spiritual integrity«.